2005
DOI: 10.1590/s0100-29452005000100020
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento de catorze porta-enxertos para o limão eureka km 47 na região de Araraquara-SP

Abstract: Foi avaliado o comportamento de 14 porta-enxertos para o limão 'Eureka km 47' [Citrus limon (L.) Burm. f.], clone nucelar, em experimento instalado em 1991, na Fazenda Fittipaldi, Araraquara-SP. Os porta-enxertos foram: tangelos 'Orlando' e 'Seminole' (C. reticulata Blanco x C. paradisi Macfad.), tangerinas 'Cleópatra' (C. reshni hort. ex Tanaka) e 'Sunki' [C. sunki (Hayata) hort. ex Tanaka], limões 'Cravo' (C. limonia Osbeck), 'Rugoso da África' (C. jambhiri Lush.) e 'Volkameriano Catania 2' (C. volkameriana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
1
2
0
2
Order By: Relevance
“…However, a reduced tree size is an interesting issue in citrus breeding programs as long as the yield efficiency is not affected, which also seems to be an interesting result of our study, because no significant differences were found in the mean fruit number and the mean yield per tree between the Ct and treated plants (Table 3). Similar results have been reported in trees grafted onto some FA hybrids, Cleopatra mandarin and C. macrophylla rootstocks [29,30]. This is also a point to favor semidwarfing materials like rootstocks FA-418 and FA-517.…”
Section: Correlation Analysissupporting
confidence: 86%
“…However, a reduced tree size is an interesting issue in citrus breeding programs as long as the yield efficiency is not affected, which also seems to be an interesting result of our study, because no significant differences were found in the mean fruit number and the mean yield per tree between the Ct and treated plants (Table 3). Similar results have been reported in trees grafted onto some FA hybrids, Cleopatra mandarin and C. macrophylla rootstocks [29,30]. This is also a point to favor semidwarfing materials like rootstocks FA-418 and FA-517.…”
Section: Correlation Analysissupporting
confidence: 86%
“…Figueiredo et al [2] reported an average fruit yield of the first three harvest years (4th to the 6th year after planting) of Tahiti on 11 rootstocks, planted in a density of 208 trees⋅ha -1 , in Brazil. In this research, the greatest productivity was induced by Orlando tangelo (9.88 t⋅ha -1 ), Morton citrange (9.82 t⋅ha -1 ), Rangpur lime (7.6 t⋅ha -1 ), Poncirus trifoliata (7.36 t⋅ha -1 ), Volkamer [12].…”
Section: Discussionmentioning
confidence: 99%
“…Scion is based on just two selections, the IAC-5 or Peruano, and the Quebra-Galho varieties. Trees are grafted mostly on Rangpur lime (Citrus limonia Osbeck) due to its traditional use and lack of more studies on alternative rootstocks [2]. These scion/rootstock combinations have a short commercial life, because of a poor tolerance to Phytophtora spp., present in many groves, and contaminations with severe strains of tristeza, and with exocortis in the case of the Quebra-Galho selection [3].…”
Section: Introductionmentioning
confidence: 99%
“…Do sétimo ao décimo primeiro ano, o C. pennivesiculata confirmou seu melhor desempenho frente aos outros, alcançando uma produção média de 250 kg planta -1 (FIGUEIREDO et al, 2005).…”
Section: Porta-enxertos Para Limeira áCida "Tahiti"unclassified